2022
DOI: 10.1007/s11357-022-00572-w
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of γδ T cells in visceral fat with aging promotes chronic inflammation

Abstract: Adipose tissue dysfunction is strongly linked to the development of chronic inflammation and cardiometabolic disorders in aging. While much attention has been given to the role of resident adipose tissue immune cells in the disruption of homeostasis in obesity, age-specific effects remain understudied. Here, we identified and characterized a population of γδ T cells, which show unique age-dependent accumulation in the visceral adipose tissue (VAT) of both mice and humans. Diet-induced obesity likewise increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…BMI is a good screening tool for obesity in the population, but it does not seem to be a good indicator for predicting the prognosis of total knee arthroplasty. It is worth noting that the factors that cause adverse effects after total knee arthroplasty due to obesity include local inflammation caused by fat accumulation, chronic inflammation and pain susceptibility caused by hyperlipidemia, biomechanical changes caused by high weight, and various complications caused by obesity [20][21][22][23]. Of these indicators, only higher weight may be closely associated with BMI, while the rest can be better evaluated individually independent of BMI.…”
Section: Resultsmentioning
confidence: 99%
“…BMI is a good screening tool for obesity in the population, but it does not seem to be a good indicator for predicting the prognosis of total knee arthroplasty. It is worth noting that the factors that cause adverse effects after total knee arthroplasty due to obesity include local inflammation caused by fat accumulation, chronic inflammation and pain susceptibility caused by hyperlipidemia, biomechanical changes caused by high weight, and various complications caused by obesity [20][21][22][23]. Of these indicators, only higher weight may be closely associated with BMI, while the rest can be better evaluated individually independent of BMI.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether these cells are protective or deleterious in fibrosis appears to be tissue- and context-dependent 88,89 . For instance, age-related accumulation of Type 17 γδTs contributes to chronic inflammation in adipose tissue 90 . In the ovary, expansion of the Type 17 γδTs could either promote fibrosis or be a compensatory attempt to dampen the fibrotic environment.…”
Section: Discussionmentioning
confidence: 99%
“…This increase occurs independent of adiposity and without regard for sex. In the absence of γδ T cells (TCRδ KO mice), inflammation, both locally in VAT and systemically, is reduced in aged mice confirming a role for these cells in age-associated inflammation ( Bruno et al, 2022 ). Deficiency of γδ T cells in old age also improved the metabolic phenotype characterized by increased respiratory exchange ratio.…”
Section: Introductionmentioning
confidence: 88%
“…We recently reported that γδ T cells are increased by aging in VAT of mice and humans ( Bruno et al, 2022 ). This increase occurs independent of adiposity and without regard for sex.…”
Section: Introductionmentioning
confidence: 99%